2017
DOI: 10.1063/1.5008909
|View full text |Cite
|
Sign up to set email alerts
|

Plasma flow modeling for Huels-type arc heater with turbulent diffusion

Abstract: In this study, we developed an analytical model for the flow field in the Huels-type arc-heated wind tunnel (L2K) of the German Aerospace Center. This flow-field model can be used to accurately reproduce the discharge behavior in the heating section and expansion in the nozzle section of L2K. It includes the radiation transport and turbulent flow, as well as thermochemical nonequilibrium models, which are tightly coupled with electric field calculations. In addition, we considered the turbulent diffusion model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Sahai et al [25] numerically investigated a three-dimensional unsteady arc-heated flow. Takahashi et al [26][27][28][29] conducted plasma flow analyses of a 20 kW constrictor-type Japan Aerospace Exploration Agency (JAXA) arc-heated wind tunnel and a DLR arc-heated wind tunnel. These studies revealed the importance of turbulence and radiative heat transport in the heating section, as well as of thermochemical nonequilibrium in the nozzle and test chamber regions.…”
Section: Introductionmentioning
confidence: 99%
“…Sahai et al [25] numerically investigated a three-dimensional unsteady arc-heated flow. Takahashi et al [26][27][28][29] conducted plasma flow analyses of a 20 kW constrictor-type Japan Aerospace Exploration Agency (JAXA) arc-heated wind tunnel and a DLR arc-heated wind tunnel. These studies revealed the importance of turbulence and radiative heat transport in the heating section, as well as of thermochemical nonequilibrium in the nozzle and test chamber regions.…”
Section: Introductionmentioning
confidence: 99%